Strongyloides stercoralis combined with concurrent multiple pathogens infections in an immunosuppressed patient: a case report - Fang, Jingchun; Fang, Huimin; Guo, Penghao; Peng, Yaqin; Chen, Peisong (Frontiers in Medicine, 2025)
BackgroundStrongyloides stercoralis is an opportunistic pathogenic parasite. Most individuals with normal immune function may not exhibit significant symptoms, and the signs are atypical, which can easily lead to missed diagnoses and delayed treatment. People with underlying diseases and weakened immunity are prone to develop severe conditions after infection with Strongyloides stercoralis.Case presentationWe report an immunocompromised patient in whom the pathogen was initially not detectable using traditional parasitic detection techniques. However, Strongyloides stercoralis was identified in both the alveolar lavage fluid and blood through metagenomic next-generation sequencing. Subsequently, Strongyloides stercoralis was detected in the alveolar lavage fluid after multiple rounds of testing using traditional microscopic examination techniques. Based on the mNGS results and other examination findings, the patient was diagnosed with Strongyloides stercoralis in combination with concurrent multiple pathogens infections. After the combined drug therapy of Meropenem, Vancomycin, and Albendazole, the patient’s condition was gradually brought under control.ConclusionThis case demonstrates the advantage of integrating traditional detection methods with metagenomics next-generation sequencing technology in the etiological diagnosis of immunocompromised individuals. It is conducive to clarifying the etiological diagnosis of patients and thereby facilitating the timely initiation of corresponding treatments.